2018
DOI: 10.1055/a-0596-7531
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physical Activity Level and Pelvic Floor Muscle Variables in Women

Abstract: In order to investigate the potential impact of physical activity (PA) on pelvic floor muscle (PFM) function, a cross-sectional study was made to analyse the association between PA level and vaginal resting pressure (VRP) and PFM strength and endurance. Thirty-eight continent women and 20 women with stress urinary incontinence (SUI) aged 19 to 49 years were enrolled in the study. PFM variables were assessed by manometry. The PA level was assessed through the International Physical Activity Questionnaire – Shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…Health care professionals may hypothesize that lack of physical activity would cause weaker pelvic floor muscles and thus induce leakage. However, no association between physical activity level and pelvic floor muscle strength and endurance has been reported among non-cancer women (n = 58) [34]. Based on previous findings [20,22,[30][31][32][33][34], it seems more plausible that the leakage induced reduced physical activity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Health care professionals may hypothesize that lack of physical activity would cause weaker pelvic floor muscles and thus induce leakage. However, no association between physical activity level and pelvic floor muscle strength and endurance has been reported among non-cancer women (n = 58) [34]. Based on previous findings [20,22,[30][31][32][33][34], it seems more plausible that the leakage induced reduced physical activity.…”
Section: Discussionmentioning
confidence: 92%
“…However, no association between physical activity level and pelvic floor muscle strength and endurance has been reported among non-cancer women (n = 58) [34]. Based on previous findings [20,22,[30][31][32][33][34], it seems more plausible that the leakage induced reduced physical activity. The findings that survivors who smoke and/or are less well educated practiced less physical activity are in line with findings among non-cancer general populations [35][36][37] and among cancer survivors participating in rehabilitation groups [29].…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, another cross-sectional study found no association between physical activity level, assessed by questionnaire, and vaginal resting pressure, PFM strength and endurance [43]. However, there was a weak positive association between physical activity level in continent women and a weak negative association in incontinent women [43].…”
Section: Evidence Suggesting No Difference In Pfm Strengthmentioning
confidence: 93%
“…In a cross-sectional analysis of 203 primiparous women 1 year postpartum, there were no significant associations between PFM force and measures of strength and fitness, including grip strength, trunk flexor endurance duration, percent body fat, or self-reported physical activity [42]. Similarly, another cross-sectional study found no association between physical activity level, assessed by questionnaire, and vaginal resting pressure, PFM strength and endurance [43]. However, there was a weak positive association between physical activity level in continent women and a weak negative association in incontinent women [43].…”
Section: Evidence Suggesting No Difference In Pfm Strengthmentioning
confidence: 93%
“…In our study, the relationship between the presence of constipation and stress urinary incontinence was found to be statistically significant, and the result was parallel to the literature. Stress urinary incontinence was found to be lower in women with higher levels of physical activity, but it was found that women with stress urinary incontinence did not prefer some physical activities and decreased physical activities [24,25]. Nygaard et al in their study, has found that physical activity such as jumping increased the incidence of stress urinary incontinence [26].…”
Section: Discussionmentioning
confidence: 94%